A non-invasive intratracheal inoculation method for the study of pulmonary melioidosis - Revelli, David A.; Boylan, Julie A.; Gherardini, Frank C. (Frontiers in Cellular and Infection Microbiology, 2012)
Pulmonary melioidosis, a disease manifestation caused by the bacterium Burkholderia pseudomallei, has been studied using aerosols or intranasal (IN) inoculation in small animal models. Both have inherent disadvantages which may not accurately model primary pulmonary melioidosis in humans. Intratracheal inoculation (IT) by direct visualization of the tracheal opening offers an alternative technique for infection that overcomes the disadvantages of aerosol and IN challenge. In this study, we describe a method which requires relatively inexpensive equipment, little training, and is compliant with the operational constraints of a BSL3 laboratory. Results obtained using trypan blue demonstrated that an inoculum can be accurately delivered into the lungs of mice within a biosafety cabinet (BSC). Whole body imaging and histopathology confirmed that mice inoculated intratracheally with B. pseudomallei develop the primary focus of infection in the lungs, and not the nasal passages which can lead to invasion of the central nervous system and potential neurologic complications. Further, based on colony counts and bioluminescent imaging, dissemination to secondary organs occurred as expected. Taken together, this intratracheal method of inoculation fulfills four goals: (1) to accurately deliver B. pseudomallei into the lungs of the animal model, (2) to avoid potentially confounding complications due to primary infections at sites other than the lung, (3) to maintain normal organ dissemination, and (4) to be BSL3 compliant.